Factors affect bank performance under the mediator role of environmental management accounting: evidence in Vietnam - Trung Nguyen Kim Quoc; Lien Duong Thi Thuy (Cogent Business & Management, 2025)
This study examines the mediating role of environmental management accounting (EMA) in the effect of contingency theory factors on bank performance in Vietnam. The research employs qualitative methods (such as expert interviews and surveys) and quantitative methods (partial least squares structural equation modeling (PLS-SEM). We surveyed 315 respondents across the banking sector in Vietnam, particularly Ho Chi Minh City. The findings reveal an indirect relationship between environmental strategy, organizational structure, industry, organizational size, green innovation, and bank performance under the EMA intervention. This study underscores the role of the EMA in enhancing bank performance and benefiting all other stakeholders. This means that policymakers should focus on the mediating role of EMA in enhancing and improving bank performance.